2020
DOI: 10.3390/ijerph17020458
|View full text |Cite
|
Sign up to set email alerts
|

A Chance-Constrained Vehicle Routing Problem for Wet Waste Collection and Transportation Considering Carbon Emissions

Abstract: In order to solve the optimization problem of wet waste collection and transportation in Chinese cities, this paper constructs a chance-constrained low-carbon vehicle routing problem (CCLCVRP) model in waste management system and applies certain algorithms to solve the model. Considering the environmental protection point of view, the CCLCVRP model combines carbon emission costs with traditional waste management costs under the scenario of application of smart bins. Taking into the uncertainty of the waste gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Responding data as the low carbon society concept idea: it focuses on the procedure design as the sustainable development to reduce the green gas effect from the transforming procedure of wet garbage as the artificial soil causing the increasing expenditure or gaining the new procedure as the result to promote the low carbon society (Shams, S., et al, 2017), as well as reducing the releasing of Co2 in transformation procedure suitably (da Graça Carvalho, M., et al, 2011;Wu, H., et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Responding data as the low carbon society concept idea: it focuses on the procedure design as the sustainable development to reduce the green gas effect from the transforming procedure of wet garbage as the artificial soil causing the increasing expenditure or gaining the new procedure as the result to promote the low carbon society (Shams, S., et al, 2017), as well as reducing the releasing of Co2 in transformation procedure suitably (da Graça Carvalho, M., et al, 2011;Wu, H., et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This paper randomly selects 8 cases from the database including small-scale study (Pro1, Pro2, Pro3, Pro4), medium-scale study (Pro5, Pro6, Pro7) and large-scale study (Pro8), the detailed information is shown in Table 5. Parameters of vehicles are shown in Table 6 according to references [21,50,51] and parameters of the proposed algorithm are shown in Table 7 according to references [10,[52][53][54].…”
Section: Test Casesmentioning
confidence: 99%
“…Parameters of vehicles are shown in Table 6 according to references [ 21 , 50 , 51 ] and parameters of the proposed algorithm are shown in Table 7 according to references [ 10 , 52 , 53 , 54 ].…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Traditional exact methods are only applicable to small problem instances [5]. In recent years, considerable efforts have been devoted to evolutionary algorithms [6][7][8], including genetic algorithms (GA) [9][10][11][12][13], particle swarm optimization [14][15][16][17][18], ant colony optimization (ACO) [19][20][21][22][23], artificial bee colony [24][25][26], biogeography-based optimization [27,28], etc., for VRPs. Compared to exact algorithms and construction heuristics, evolutionary algorithms are more capable of jumping out of local optima and obtaining optimal or near-optimal solutions within an acceptable time by evolving a population of candidate solutions to simultaneously explore multiple regions of the search space [29].…”
Section: Related Workmentioning
confidence: 99%
“…The hybrid WWO and neighborhood search algorithm for the quarantine vehicle routing problem. 1 Use the procedures described in Section 4.1 to initialize a population P of solutions; 2 while the stopping condition is not met do 3 foreach solution Z = (X, Y) in the population do 4 Calculate the wavelength of Z according to Equation (17); 5 for d = 1 to N X do 6 Letd = rand(1, n X ); 7 Reverse the subsequence X[d,d]; 8 Call Algorithm 5 to improve the direction vector Y according to the new sequence vector X; 9 Call Algorithm 4 to improve the new solution Z by balancing the areas among the subsequences; 10 if Z is better than the original solution then 11 Replace the original solution with Z in the population; 12 if Z is the newly found best solution then 13 for i = 1 to m do 14 for k = 1 to αn i do 15 Clone Z to a new solution Z ; 16 Swap two randomly selected areas in x i ; 17 if Z is better than the Z then 18 Let Z = Z ; 19 Update the population size; 20 return the best solution found so far.…”
Section: Algorithmmentioning
confidence: 99%